MANAJEMEN MUTU SANTRI PADA PROGRAM PENDIDIKAN KESETARAAN DI MA’HAD AL-FARUQ KARANGLEWAS KABUPATEN BANYUMAS - Ali Munif (IAIN Purwokerto, 2019)
This research examines how Ma'had al-Faruq Karanglewas responses to the implementation of learning compulsory of basic program of the Ministry of Religious affairs and strategy in the enchancement of the quality of equality education programs in Ma'had al-Faruq Karanglewas, the target/goal is the quality enchance of the students. This research uses qualitative approach, with technique of collecting data of observation, interview and documentation. Furthermore, to analyze data that have been collected since the beginning of research until the end of research, using data reduction technique, data presentation, verification and conclusion. The results of research shows the strategy of quality enchancement of equality education in Ma'had al-Faruq Karanglewas Banyumas can be done by: first, focus on customer satisfaction by improving the success of students learning, giving credibility to the students parents about the success of students learning, and giving prosperity to the teachers. Second, it involve totality all the stakeholders starting from the caregivers, administrators, the council of david, the students, the community, the guardians of students and the government to apply the quality of culture. Third, making the measurement of the quality of alumnus by targeting the students can mastery the tools science , namely nahwu and shorof and can apply the yellow book, and do good deed. Fourth, build commitment, by the commitment to realize the boarding school’s goals. Fifth, doing continuous improvement starting from the input or planning, processing, until output in education in boarding school.